Prasangka sosial terhadap komunitas punk: Adakah peranan kepribadian otoritarian? - Desitasari, Nur Laili; Suhadianto; Herlan Pratikto (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between authoritarian personality and social prejudice against the punk community in Surabaya. The population in this study is the community in the district of Pacar Keling with a population of 24,137 people. There were 393 participants in this study who were obtained using the Slovin formula. The research instrument uses an Authoritarian Personality and Social Prejudice Scale. Retrieval of data in this study using the Accidental Sampling Technique. The data analysis technique in this study used Spearman’s Rho test. The result is p=0.000 (p<0.05) and rxy= 0.870, meaning that there is a significant positive relationship between authoritarian personality and social prejudice against the punk community. Suggestions in this research are that it is hoped that research participants will increase the value of tolerance and be objective in assessing other groups and for the government, in this case, social services, to play a more active role in giving attention to and empowering the potential that exists in the punk community so that it can be positive and useful for punk community or society. Keywords: Punk, Social Prejudice, Authoritarian Personality